Activity of the Ovarian Germinal Epithelium in the Freshwater Catfish, Pimelodus maculatus (Teleostei: Ostariophysi: Siluriformes): Germline Cysts, Follicle Formation and Oocyte Development - Quagio-Grassiotto, Irani [UNESP]; Grier, Harry; Mazzoni, Talita Sarah; Nobrega, Rafael Henrique; de Arruda Amorim, Joao Paulo [UNESP] (Wiley-Blackwell, 2011)
Distinct types of oogonia are found in the germinal epithelium that borders the ovarian lamellae of Pimelodus maculatus: A-undifferentiated, A-differentiated and B-oogonia. This is similar to the situation observed for spermatogonia in the vertebrate testis. The single A-undifferentiated oogonia divide by mitosis giving rise to A-groups of single differentiated oogonia, each enclosed by epithelial cells that are prefollicle cells. Subsequently, the single A-differentiated oogonia proliferate to generate B-oogonia that are interconnected by cytoplasmic bridges, hence, forming germline cysts. The prefollicle cells associated with them also divide. Within the germline cysts, B-oogonia enter meiosis becoming oocytes. Meiotic prophase and early folliculogenesis occur within the germline cysts. During folliculogenesis, prefollicle cells grow between the oocytes, encompassing and individualizing each of them. The intercellular bridges disappear, and the germline cysts are broken down. Next, a basement membrane begins to form around the nascent follicle, separating an oocyte and its associated prefollicle cells from the cell nest. Folliculogenesis is completed when the oocyte and the now follicle cells are totally encompassed by a basement membrane. Cells derived from the ovarian stroma encompass the newly-formed ovarian follicle, and become the theca, thereby completing the formation of the follicle complex. Follicle complexes remain attached to the germinal epithelium as they share a portion of basement membrane. This attachment site is where the oocyte is released during ovulation. The postovulatory follicle complex is continuous with the germinal epithelium as both are supported by a continuous basement membrane. The findings in P. maculatus reinforce the hypothesis that ovarian follicle formation represents a conserved process throughout vertebrate evolution. J. Morphol. 272:1290-1306, 2011. (C) 2011Wiley-Liss, Inc.
Keywords: germinal epithelium; germ cell nest; germline cyst; folliculogenesis; oocyte development; catfish Pimelodus maculatus